ANALISIS KONTRIBUSI DAN EFEKTIVITAS SUMBER-SUMBER PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PEMERINTAH DAERAH KOTA SUKABUMI - Adawiyah, W; Kusuma, Indra Cahya (Fakultas Ekonomi Universitas Djuanda, 2015)
The aim this research is to analyze the contribution and effectiveness of sources of local government income and Fund Balance toward Income and Expenditure Budget in Local Government of Sukabumi. The research used secondary data and unit of analysis was Report of Income and Expenditure Budget Calculation period 2006-2010. Analysis used in this research was analysis of contribution and effectiveness analysis.The result shows that the income contribution from local government income to the Local Government Budget from 2006 to 2010 average 13.55% annually and fluctuated and less base on the criteria. The Contribution of Fund Balance to the Local Government Budget from 2006 to 2010 average 75.53% annually. Level of effectiveness of local income tax, levies, local wealth management, and other legitimate income in from 2006 to 2010 was very good, when the realization can exceed the set targets and runs fluctuate from year to year. The General Allocation Fund and Special Allocation Fund Sukabumi encounter situations where the targets set in accordance with the actual revenues that is equal to 100% (effective).Keywords : Contributions, effectiveness, sources of Income, Fund Balance, Local Government Sukabumi